2015
DOI: 10.1103/physrevb.92.201301
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-frequency quantum beats of quantum confined exciton states

Abstract: Multiple quantum beats of a system of the coherently excited quantum confined exciton states in a high-quality heterostructure with a wide InGaAs/GaAs quantum well are experimentally detected by the spectrally resolved pump-probe method for the first time. The beat signal is observed as at positive as at negative delays between the pump and probe pulses. A theoretical model is developed, which allows one to attribute the QBs at negative delay to the four-wave mixing (FWM) signal detected at the non-standard di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Therefore, their coherent coupling strengths are different, and the contribution to a coherent superposition is not evenly distributed. Therefore, the dominant fine states determine multiple QB periods, and the rest of fine states give negligible QB amplitudes in the Fourier‐transformed frequency spectrum.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Therefore, their coherent coupling strengths are different, and the contribution to a coherent superposition is not evenly distributed. Therefore, the dominant fine states determine multiple QB periods, and the rest of fine states give negligible QB amplitudes in the Fourier‐transformed frequency spectrum.…”
mentioning
confidence: 79%
“…For DFWM signals, we have calculated transient optical nonlinearities of the fine levels in a GaAs/AlGaAs QR by utilizing the semiconductor Bloch equation. When the fine levels of a QR are excited by a pair of picosecond laser pulses, we found that quantum beats (QBs) appear, where time‐integrated DFWM signals oscillate for increasing delay time between the two pulses. The oscillation periods of multiple QBs are dominated by the energy difference of the dominant fine levels, and this method enables to detect a spectral shift of the fine levels for applying an external magnetic field.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed characteristics of the sample and experimental details can be found in Refs. [29,30]. Figure 5 shows intensities of the pump-probe signals measured at energies corresponding to transitions to the first and fourth quantum-confined levels.…”
Section: Discussionmentioning
confidence: 99%